2021
DOI: 10.3390/nu13124309
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Isolated and Combined Application of Menthol and Carbohydrate Mouth Rinses on 40 km Time Trial Performance, Physiological and Perceptual Measures in the Heat

Abstract: The current study compared mouth swills containing carbohydrate (CHO), menthol (MEN) or a combination (BOTH) on 40 km cycling time trial (TT) performance in the heat (32 °C, 40% humidity, 1000 W radiant load) and investigates associated physiological (rectal temperature (Trec), heart rate (HR)) and subjective measures (thermal comfort (TC), thermal sensation (TS), thirst, oral cooling (OC) and RPE (legs and lungs)). Eight recreationally trained male cyclists (32 ± 9 y; height: 180.9 ± 7.0 cm; weight: 76.3 ± 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(28 citation statements)
references
References 66 publications
2
26
0
Order By: Relevance
“…Results showed no significant differences between beverages with all perceptual measures increasing over time. In a longer duration time trial over 40 km when MEN rinsing was compared to carbohydrate (CHO) or a MEN+ CHO rinse, similar findings were observed [ 35 ]. Menthol solutions did induce elevated localised sensations of oral cooling, but given extended exercise duration it was thought that glycogen reduction was a more deleterious signal than alterations in thermal perception as a result of exercise associated heat storage [ 35 ].…”
Section: Discussionsupporting
confidence: 55%
See 4 more Smart Citations
“…Results showed no significant differences between beverages with all perceptual measures increasing over time. In a longer duration time trial over 40 km when MEN rinsing was compared to carbohydrate (CHO) or a MEN+ CHO rinse, similar findings were observed [ 35 ]. Menthol solutions did induce elevated localised sensations of oral cooling, but given extended exercise duration it was thought that glycogen reduction was a more deleterious signal than alterations in thermal perception as a result of exercise associated heat storage [ 35 ].…”
Section: Discussionsupporting
confidence: 55%
“…In a longer duration time trial over 40 km when MEN rinsing was compared to carbohydrate (CHO) or a MEN+ CHO rinse, similar findings were observed [ 35 ]. Menthol solutions did induce elevated localised sensations of oral cooling, but given extended exercise duration it was thought that glycogen reduction was a more deleterious signal than alterations in thermal perception as a result of exercise associated heat storage [ 35 ]. Gavel et al [ 16 ], state that several previous studies have seen lower thermal perceptual measures however, there have been an equal number of studies reviewed that have observed no change at all, especially with increased exercise intensity.…”
Section: Discussionsupporting
confidence: 55%
See 3 more Smart Citations